Case reviews in ophthalmology - Friedman, Neil J.; Kaiser, Peter K. (Elsevier, 2018)
"The case study format used in Case Reviews in Ophthalmology, 2nd Edition has been proven to be a highly effective way to incorporate medical knowledge with clinical judgment - resulting in the best possible results on practical exams. More than 140 relevant cases cover every aspect of the field: optics/refraction; neuro-ophthalmology/orbit; pediatrics/strabismus; external disease/adnexa; anterior segment; and posterior segment. Large photos highlight each case, enhancing your knowledge and reinforcing key aspects of diagnosis."--Publisher
Preface Acknowledgements Chapter 1: Optics/Refraction Chapter 2: Neuro-Ophthalmology/Orbit Chapter 3: Pediatric Ophthalmology/Strabismus Chapter 4: External Disease/Adnexa Chapter 5: Anterior Segment Chapter 6: Posterior Segment Index. - Includes indexes
Keywords: Eye / Diseases; Ophthalmology; Eye Diseases; Eye -- Diseases -- Case studies; Ophthalmology -- Case studies